1996
DOI: 10.1002/(sici)1099-1034(199606)31:2<179::aid-gj708>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb geochronology of Late Palaeozoic plutons, Cobequid Highlands, Nova Scotia, Canada: evidence for Late Devonian emplacement adjacent to the Meguma-Avalon terrane boundary in the Canadian Appalachians

Abstract: The Cobequid Highlands in the Canadian Appalachian orogen lie within Avalonia adjacent to the Meguma Terrane. IJ -Pb (zircon) data show that the age range of voluminous bimodal plutonism in the highlands is from 358 to 363 Ma (late Devonian). This age range is much narrower than that previously suggested by Rb/Sr geochronology and confirms that the Cobequid Highlands preserve the youngest large-scale plutonic event in the Canadian Appalachians. Late Palaeozoic tectonic history of the Appalachian orogen is prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Radiometric ages interpreted to date igneous events are shown, based on U-Pb dates on zircon by Doig et al (1996) and Dunning et al (2002) (shown in italic font) and Ar-Ar dating principally of amphibole by Pe- Piper et al (2004) (shown in regular font). * Indicates ages of coeval volcanic rocks (Clemens 1998), and this concomitantly attests to fault control on the ascent and emplacement of plutons, several problems remain regarding the concept of faults and plutons (Vigneresse 1995;Cruden 1998).…”
Section: General Problems Of Fault Control On Pluton Emplacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiometric ages interpreted to date igneous events are shown, based on U-Pb dates on zircon by Doig et al (1996) and Dunning et al (2002) (shown in italic font) and Ar-Ar dating principally of amphibole by Pe- Piper et al (2004) (shown in regular font). * Indicates ages of coeval volcanic rocks (Clemens 1998), and this concomitantly attests to fault control on the ascent and emplacement of plutons, several problems remain regarding the concept of faults and plutons (Vigneresse 1995;Cruden 1998).…”
Section: General Problems Of Fault Control On Pluton Emplacementmentioning
confidence: 99%
“…Almost all pluton emplacement may have taken place over a period of <5 Ma from 363 to 358 Ma, based on reported dates that have standard errors of ±2-4 Ma (Doig et al 1996;Pe-Piper et al 2004) (Table 1), although the precision of dating means that pluton emplacement might have extended over as much as 10 Ma. The only exceptions are the late gabbro in the southwestern Wentworth pluton (Fig.…”
Section: Geological Setting Of the Plutons In Cobequid Shear Zonementioning
confidence: 99%
“…The emplacement of these plutonic rocks thus straddles the Devonian-Carboniferous boundary. The granitic Gilbert Hills Doig et al (1996) and Dunning et al (2002); 40 Ar/ 39 Ar dating from Nearing et al (1996); palynology summarized in Dunning et al (2002). pluton in the north central Cobequid Highlands is probably of similar age.…”
Section: Late Devonian -Early Carboniferous Plutonic Rocksmentioning
confidence: 99%
“…In the Meguma terrane, the Early Paleozoic sequence is intruded by c. 382-357Ma plutons (including the South Mountain and Musquodoboit batholiths, Clarke et al, 1997;Tate and Clarke, 1995). In Nova Scotia, the Late Devonian sequence comprises sedimentary rocks interbedded with volcanic rocks (Doig et al, 1996;Murphy et al, 2018;Pe-Piper et al, 2004). Zircon and monazite U-Pb ages obtained from from granulite facies metasedimentary xenoliths from a Late Devonian mafic dyke that intrudes the Meguma terrane, yielded three age groups at c. 399, 377 and 354Ma, interpreted as representing metamorphic events (Greenough et al, 1999;Shellnutt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%